(untitled) (Bangladesh Medical Journal, 2014)
The "doctor-patient" relationship (DPR) or the "physician-patient" relationship (PPR) has long been recognized as a complex, multifaceted, and complicated balance of engagement between the care-seeker and the care-giver. The physician-patient relationship is central to the practice of healthcare and is essential for the delivery of high-quality health care in the diagnosis and treatment of disease. The doctor-patient relationship forms one of the foundations of contemporary medical ethics. In the present moment doctor-patient relationship (DPR) or physician-patient relationship (PPR) is one of the major issues in health-care throughout the world. The most common complains about the physicians of Bangladesh is their attitude towards the patients. The patients must have confidence in the competence of doctors and should feel that they can confide in him or her. For physicians, the establishment of a good relationship with the patients is also important. In developed countries students are taught from the beginning, even before they set foot in hospitals, to maintain a professional relationship with the patients, to uphold patients’ dignity, and respect their privacy. These are deficient in Bangladesh. In addition to service factors, perceived treatment cost is another factor that patients may perceive as excessive. This special article reflects the importance as well as the necessary elements to establish this sacred relationship. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18786 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 55-58